PENGEMBANGAN AGROINDUSTRI GULA KELAPA DI KABUPATEN CILACAP: KAJIAN STRATEGI MARKETING HASIL PERTANIAN - Nariswari Novi Pudyastuti; Masyhuri Masyhuri; Any Suryantini (Jurnal Kawistara, 2019)
Coconut sugar industry as a part of agroindustry has given significances in regional agriculture development, however  it has not yet met the businessman needs because of the lack significant industrial development and marketing efficiency. Therefore, this study aims at identifying both the external and internal factors influencing the marketing development and formulating the alternative marketing strategies for coconut sugar products especially in Jeruklegi and Kawunganten Dirstrict of Cilacap Regency. This area is chosen based on certain considerations and this study involves 47 respondents. The methods used in this study are instrument test analysis, descriptive analysis to identify the internal and external factors, and SWOT analysis to formulate the alternative strategies for coconut sugar industry development. The result showes that generally there is still lack of quality of human resources, based on validity and reliability tests there are eight internal and ten externals factors influencing the coconut sugar marketing in Cilacap Regency. The industrial position is in cell IV which means in a stable phase, meanwhile, the main alternative strategy that can be applied in coconut sugar marketing development in Cilacap Regency is quadrant 1 namely the SO (Strengths Opportunities) strategy, it includes optimizing the production capacity, expanding the sale area, and increasing the promotional activities. Other supporting alternative strategies that consist of ST strategies (Strength Threats), WO (Weaknesses Opportunities), and WT (Threats Weaknesses) are increasing the use of production equipment technology, increasing marketing efficiency, increasing the market price knowledge, maintaining product quality, choosing managers to form beneficiary group, cooperating among villages, improving the production cleanliness, looking for funds from cooperatives in other areas for business capital, and establishing the information service center.